1987
DOI: 10.1104/pp.83.3.628
|View full text |Cite
|
Sign up to set email alerts
|

Protein Modulase Appears to Be a Complex of Ferredoxin, Ferredoxin/Thioredoxin Reductase, and Thioredoxin

Abstract: Protein modulase and ferredoxin/thioredoxin reductase are soluble proteins that have been suggested to catalyze the light-dependent modulation of enzyme activity in the stromal compartment of the chloroplast. Protein modulase is active in vitro without additional ferredoxin and thioredoxin, whereas ferredoxin/thioredoxin reductase requires additional ferredoxin and thioredoxin. We hypothesize that protein modulase is a complex protein composed of ferredoxin/thioredoxin reductase, ferredoxin, and thioredoxin. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The components involved in the transfer of electrons from photosystem I to the target enzymes are ferredoxin, FFR and thioredoxin (for reviews see Buchanan 1984, While ferredoxin is also a constituent of the electron transport chain, FTR is a typical component of the light modulation system and is quite different from FNR involved in NADP* reduction, Thioredoxins are small redox-active proteins found in all organisms. They are involved in various celltitar reductive reactions (for a review see Holmgren 1985), Common to all thioredoxins is the active site sequence -Tip-Cys-Gly-Pro-Cys-Lys-, In addition to thioredoxin^ (preferentially activating NADP*-MDH) which exhibits high overall homoiogy to most other thioredoxins, green piant tissues contain thioredoxin, (mainly specific for FBPase), which has much less similarity to the rest of the thioredoxins apart from the conserved sequence at the active site (Tsugita et al, 1983), Alternative components of a hght modulation system reported previously, namely ferraltedn (de la Torre et al, 1982) and protein moduiase , have now been resolved as complexes of varying composition containing the above-mentioned proteins (Droux et al 1987, Ford et al, 1987, The nature of a membrane-bound LEM suggested to be involved in iight modulation of enzymes has not yet been elucidated , Although the components of the ferredoxin/thioredoxin system appear to be largely soluble, specific interactions among themselves, with the thylakoids, and also with the target enzymes have been described (see e.g, Scheibe and Beck 1979), Specific interactions between the components of the lightactivation system and the target enzymes allow for the use of ferredoxin-and thioredoxin-sepharose as affinity supports for purification as suggested by PW and L6pez-Gorge (1981), The specific binding between thioredoxin and chioropiast FBPase has been investigated in detail (Soulie et al, 1985),…”
Section: Ai Components Of a Ught/darii Modubtkhi Systemmentioning
confidence: 96%
“…The components involved in the transfer of electrons from photosystem I to the target enzymes are ferredoxin, FFR and thioredoxin (for reviews see Buchanan 1984, While ferredoxin is also a constituent of the electron transport chain, FTR is a typical component of the light modulation system and is quite different from FNR involved in NADP* reduction, Thioredoxins are small redox-active proteins found in all organisms. They are involved in various celltitar reductive reactions (for a review see Holmgren 1985), Common to all thioredoxins is the active site sequence -Tip-Cys-Gly-Pro-Cys-Lys-, In addition to thioredoxin^ (preferentially activating NADP*-MDH) which exhibits high overall homoiogy to most other thioredoxins, green piant tissues contain thioredoxin, (mainly specific for FBPase), which has much less similarity to the rest of the thioredoxins apart from the conserved sequence at the active site (Tsugita et al, 1983), Alternative components of a hght modulation system reported previously, namely ferraltedn (de la Torre et al, 1982) and protein moduiase , have now been resolved as complexes of varying composition containing the above-mentioned proteins (Droux et al 1987, Ford et al, 1987, The nature of a membrane-bound LEM suggested to be involved in iight modulation of enzymes has not yet been elucidated , Although the components of the ferredoxin/thioredoxin system appear to be largely soluble, specific interactions among themselves, with the thylakoids, and also with the target enzymes have been described (see e.g, Scheibe and Beck 1979), Specific interactions between the components of the lightactivation system and the target enzymes allow for the use of ferredoxin-and thioredoxin-sepharose as affinity supports for purification as suggested by PW and L6pez-Gorge (1981), The specific binding between thioredoxin and chioropiast FBPase has been investigated in detail (Soulie et al, 1985),…”
Section: Ai Components Of a Ught/darii Modubtkhi Systemmentioning
confidence: 96%
“…There is much literature on the existence of protein-protein interactions between the components of the ferredoxin-Td activation system, these interactions being responsible of erroneous activating theories earlier described: LEM factors [2], protein modulase [8] and ferralterin [18]. Close associations have also been demonstrated between ferredoxin and ferredoxin-thioredoxin reductase [11], and between Td f and FBPase [24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in zlizlo light or reductive activation of the enzyme and the differential responses between the active and inactive forms of FBPase to divalent cations, fructose bisphosphate (FBP), and pH (Buchanan et al 1971, Charles and Halliwell 198 1, Nishizawa and Buchanan 198 1) have been analyzed. Additional observations concerning the synergistic effect of divalent cations, FBP and thioredoxins on the activation and catalysis of FBPase (Hertig andWolosiuk 1983, Gontero et al 198413, Corley andWolosiuk 1985) remain to be clarified as new properties of this enzyme continue to be reported (Ford et al 1987, Marcus et al 1988.…”
mentioning
confidence: 98%
“…T h e activity of chloroplastic FBPase, a key enzyme in the reductive pentose phosphate pathway, is regulated in land plants by the ferredoxin/thioredoxin system, light-effect mediator(s), the concentration change of divalent cations, and alkalization of the chloroplast stroma. Briefly, the relatively inactive FBPase is reductively activated by the reduced thioredoxin; the activated FBPase displays greater activity under increased Mg2+ concentration and pH in the light (Buchanan 1980, Anderson 1986, Ford et al 1987. Research on higher plants, especially spinach, has been conducted on the purification and basic physicochemical and regulatory properties of the enzyme.…”
mentioning
confidence: 99%